ORGANIZATIONAL AND ECONOMIC TOOLS OF STATE POLICY FOR THE DEVELOPMENT OF THE HOUSING SECTOR - YEPIFANOVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study focuses on the importance and problems of the development of the housing stock in Ukraine, which was actualized at the stage of the post-war reconstruction of the national economy and the need to preserve the social infrastructure in Ukraine. The purpose of the study is to substantiate the organizational and economic tools of the state policy of stimulating the development of the housing construction sector. It is shown that from the point of view of state regulation, it is important to ensure the formation of a full-fledged sector of housing construction, formed from construction enterprises and elements of functional and auxiliary infrastructure (subjects of market infrastructure; real estate agencies; development structures; design bureaus; consulting, design, financial -credit institutions; investment and financial funds; manufacturers and suppliers of materials, fixed assets; certification centers and laboratories; companies servicing construction facilities, etc.). It has been proven that in order to properly stimulate the development of the housing construction sector in Ukraine, a complex of organizational and economic tools should be implemented, when the implementation of organizational tools is designed to form a high-quality management system of housing construction development processes - from central and local authorities to direct investment and construction projects. The toolkit of the economic block should focus on the formation of appropriate incentives for business entities, buyers, market and branch infrastructure entities regarding investments in housing construction, development of this industry / sector of the national economy in the direction of improving the country's social infrastructure.It has been established that the purpose of the state program in this area is to determine the implementation of the principles, mechanisms and means of implementing state policy in the field of development of the housing construction sector in Ukraine. The expected results of the implementation of state regulatory instruments are defined as: creation, development and ensuring the effective operation of the system of entities that make up the housing construction sector.
Keywords: housing stock; problems and prospects; directions and principles of development; state policy; organizational and economic tools